Graduate Student Engagement and Digital Governance in Higher Education - Miray Doğan; Hasan Arslan (Education Sciences, 2025)
This study explores graduate students’ perceptions of and experiences with digital governance in higher education, using data from semi-structured interviews with thirty participants. A qualitative research design guided the investigation, addressing six research questions related to the definition, roles, effectiveness, required skills, challenges, and opportunities of digital governance. The findings reveal varying levels of familiarity with digital governance, often linked to concepts of e-government and efficient decision-making. However, many participants lacked a deep understanding of the term. Key roles of digital governance identified include improved data management, enhanced transparency, and increased inclusivity in decision-making processes. The study also highlights significant challenges, such as inadequate infrastructure, inconsistent implementation, and a lack of formal training in digital governance. Despite these barriers, digital governance offers practical benefits, including streamlined administrative processes, better accessibility, and improved research outcomes. Participants emphasized the importance of digital skills education but noted that weak infrastructure and limited curricular integration hinder skill development. Opportunities identified include greater efficiency, expanded access to education, and better support for marginalized groups. The study concludes with recommendations for a holistic approach, combining education reform, infrastructure improvement, and stakeholder collaboration to optimize the benefits of digital governance in higher education. These insights provide valuable guidance for policymakers and educators seeking to enhance digital governance in academic institutions.